2014
DOI: 10.2322/tastj.12.tr_27
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Deflection of Potentially Hazardous Asteroids Using a Coulomb Force Attractor

Abstract: A Coulomb force attractor is studied for orbital deflection of potentially hazardous asteroids. The concept of a Coulomb force attractor is based on towing an asteroid by utilizing the mutual gravitational force and Coulomb force, induced by artificial charging, between a spacecraft and the asteroid. Particular attention is placed on evaluating the resulting change in the asteroid orbit. The electric potential distribution around the spacecraft is studied, and an analytic expression of the mutual Coulomb force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…These correspond to the values assumed in Ref. 12). For all simulations, differential equations are integrated at double precision by the fourth-order Runge-Kutta scheme.…”
Section: Numerical Simulationssupporting
confidence: 78%
See 3 more Smart Citations
“…These correspond to the values assumed in Ref. 12). For all simulations, differential equations are integrated at double precision by the fourth-order Runge-Kutta scheme.…”
Section: Numerical Simulationssupporting
confidence: 78%
“…11) To investigate the deflection distance achieved with a CFA, we formulated the dynamics, proposed multiple CFA concepts, and performed numerical simulations. 12) We concluded that a CFA can yield a greater deflection distance than can a simple GT. This paper proposes a method for controlling the position of the spacecraft in the vicinity of the asteroid.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations